Ambidextrous supply chain strategy and supply chain flexibility: the contingent effect of ISO 9001. Issue 9 (27th July 2020) - Rojo-Gallego-Burin, Araceli; Llorens-Montes, Francisco Javier; Perez-Arostegui, Maria N.; Stevenson, Mark
Abstract : Purpose: To analyze the effect of an ambidextrous supply chain strategy (ASCS) – i.e. the combination of exploration and exploitation practices – on each of the four dimensions of supply chain flexibility (SCF): information system, operating system, sourcing and distribution flexibility. Further, to evaluate the influence of implementing the ISO 9001 standard on the relationship between ASCS and SCF, and whether this certification directly affects the level of SCF. We ground our model in Resource Orchestration theory. Design/methodology/approach: To perform this study, the authors used data collected from a sample of 145 non-ISO-certified firms and 157 ISO-certified firms. Findings: ASCS does not affect all four dimensions of SCF in the same way. Rather, its effect is contingent on the presence of the ISO 9001 certification. An ASCS is shown to have a positive effect on information system flexibility irrespective of the presence of ISO 9001 certification whereas for the other three dimensions of SCF, the effect of ASCS is dependent on ISO 9001 implementation. Meanwhile, ISO 9001 implementation itself does not affect the level of SCF. Practical implications: Managers can use the findings to configure their supply chain strategy based on the specific dimension(s) of SCF they seek to develop by implementing ASCS. Further, the results inform managers about the incentives for implementing ISO 9001. Originality/value: Although prior studies have shown that an ambidextrous strategy enables firms and organizational units to adapt to the environment, there have been few prior studies on ambidexterity in a supply chain context. Further, although the extant literature has suggested that the ISO 9001 may facilitate ambidexterity, this link has remained largely theoretical. In fact, there is very little prior evidence on how the practice of ISO 9001 affects the supply chain.